2013
DOI: 10.1097/tp.0b013e31828dbbbe
|View full text |Cite
|
Sign up to set email alerts
|

Do Echocardiographic Parameters Predict Mortality in Patients With End-Stage Renal Disease?

Abstract: In patients with end-stage renal disease, multiple easily determined echocardiographic parameters, including regional wall motion abnormalities and pulmonary hypertension and/or right ventricular dysfunction, were independently associated with all-cause and cardiovascular mortality. Combining these factors in a simple score may further assist in risk stratifying patients being considered for renal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
1
27
0
1
Order By: Relevance
“…In a retrospective study, Stallworthy et al . [16] reviewed echocardiographic data of patients in renal transplantation waiting list and reported that pulmonary hypertension and/or right ventricular function was associated with an increased risk of all-cause mortality. Left ventricular dysfunction and regional wall motion abnormalities were among the independent predictors of survival in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, Stallworthy et al . [16] reviewed echocardiographic data of patients in renal transplantation waiting list and reported that pulmonary hypertension and/or right ventricular function was associated with an increased risk of all-cause mortality. Left ventricular dysfunction and regional wall motion abnormalities were among the independent predictors of survival in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, other cohort studies of patients with only mildly to moderately reduced LVF did not find an association of this parameter with mortality (17). It is noteworthy that a recent retrospective study by Stallworthy et al (18) showed an association of LVF with mortality. However, Stallworthy et al (18) had no measurements of LA2D, and therefore, this parameter was not included in their analysis.…”
Section: Discussionmentioning
confidence: 93%
“…It is noteworthy that a recent retrospective study by Stallworthy et al (18) showed an association of LVF with mortality. However, Stallworthy et al (18) had no measurements of LA2D, and therefore, this parameter was not included in their analysis.…”
Section: Discussionmentioning
confidence: 95%
“…At the same time there are numerous observations of improvement in PHT along with other echocardiographic parameters after renal transplantation [1,12,25,26]. This has led many to propose that PHT can be used as an indication for expeditious renal transplantation [12,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A clear cutoff of severity of pulmonary artery pressures beyond which mortality risk increases is not well defined. It has been suggested that patients with mild to moderate PHT may be considered for expedited transplantation to prevent the PHT from worsening and potentially improve it [1,12,25,26] and severe PHT may be treated before transplantation to improve patient and graft outcomes.…”
Section: Discussionmentioning
confidence: 99%